Women development through cookery and bakery skill – A case study (International Journal of Food and Nutritional Sciences, 2022)
The aim of the study was to find impact of imparting cookery and bakery skill towomen by either government or private institutions. In order to collect primary data thequestionnaire was prepared and data collected with direct visit and interaction along with women